The transcriptome of the entomopathogenic fungus Culicinomyces clavisporus contains an ortholog of the insecticidal ribotoxin Hirsutellin - Dana Foresman; Aurélien Tartar (PeerJ, 2023)
The entomopathogenic fungus Culicinomyces clavisporus is known to infect and kill mosquito larvae and therefore has been seen as a potential biological control agent against disease vector mosquitoes. Whereas most fungal entomopathogens infect hosts by penetrating the external cuticle, C. clavisporus initiates infection through ingestion (per os). This unique infection strategy suggests that the C. clavisporus genome may be mined for novel pathogenicity factors with potential for vector control. To this end, an Isoseq-based transcriptome analysis was initiated, and resulted in a total of 3,512,145 sequences, with an average length of 1,732 bp. Transcripts assembly and annotation suggested that the C. clavisporus transcriptome lacked the cuticle-degrading proteins that have been associated with other entomopathogenic fungi, supporting the per os pathogenicity process. Furthermore, mining of the sequence data unexpectedly revealed C. clavisporus transcripts homologous to the Hirsutellin toxin. Comparative sequence analyses indicated that the C. clavisporus Hirsutellin predicted protein has retained the canonical molecular features that have been associated with the ribotoxic and insecticidal properties of the original toxin isolated from Hirsutella thompsonii. The identification of an Hirsutellin ortholog in C. clavisporus was supported by phylogenetic analyses demonstrating that Culicinomyces and Hirsutella were closely related genera in the Ophiocordycipitaceae family. Validation of the mosquitocidal activity of this novel C. clavisporus protein has yet to be performed but may help position Hirsutellin orthologs as prime candidates for the development of alternative biocontrol approaches complementing the current toolbox of vector mosquito management strategies.